230k views
4 votes
Find the sum (3p^2 +3p -2) + (-6p^2 +5p -5)

2 Answers

3 votes

Let's simplify step-by-step.

3p2+3p−2−6p2+5p−5

=3p2+3p+−2+−6p2+5p+−5

Combine Like Terms:

=3p2+3p+−2+−6p2+5p+−5

=(3p2+−6p2)+(3p+5p)+(−2+−5)

=−3p2+8p+−7

So, the answer for this problem is −3p2+8p+−7.

User Exlord
by
4.8k points
6 votes

Answer:

all work is shown and pictured

Find the sum (3p^2 +3p -2) + (-6p^2 +5p -5)-example-1
User Jschimpf
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.